Consumption of Wheat Peptides Improves Functional Constipation: A Translational Study in Humans and Mice. Issue 19 (9th August 2022) - Wang, Qianqian; Shen, Fei; Zhang, Junhui; Cai, Haiying; Pan, Ya; Sun, Tengjia; Gong, Yihang; Du, Juan; Zhong, Hao; Feng, Fengqin
Abstract : Scope: Wheat peptides (WP) are rich in glutamic acid, glutamine, and other bioactive compounds that may benefit gut function and health. This study aims to evaluate the effects of regular consumption of WP on constipation‐induced complications and gut microbiota in humans and mice. Methods and results: A randomized trial of 49 functional constipation participants is conducted. The weekly amount of spontaneous bowel movements (SBM) increases by 2.09 per week after WP treatment, and by 0.40 per week among the placebo group (PL). Concomitantly, the secondary outcomes show significant improvements in the quality of life‐related to constipation (PAC‐QOL), constipation severity, and satisfaction with the intervention. In the animal study, WP effectively alleviates constipation symptoms and affects the secretion of intestinal mobility‐related neurotransmitters and gastrointestinal hormones in loperamide‐induced constipation mice. Additionally, WP regulates the gene and protein expression levels of water‐electrolyte metabolism and intestinal mobility. Furthermore, WP treatment decreases the abundance of several gut microbiota positively correlated to constipation ( Turicibacter, Bacteroides_f_Bacteroidaceae, and Streptococcus ) in mice. Conclusion: WP ameliorates constipation in humans and mice, which could be partly explained by improving water‐electrolyte metabolism, boosting intestinal motility, and reshaping gut microbiota. Abstract : A randomized, placebo‐controlled trial is carried out in functional constipation participants that received wheat peptides for 4 weeks. In parallel, a study is performed in constipation mice that oral administered wheat peptides for 2 weeks. WP supplementation ameliorates constipation symptoms in humans and mice, potentially by improving water‐electrolyte metabolism, boosting intestinal motility, and remolding the structure of disbalanced gut microbiota.